In vitro ruminal fermentation kinetics of different agroindustrial co-products used in ruminant diets - Ferro, M. M.; Costa, F. G.; de Moura, D. C.; Costa, R. V. [UNESP]; de Oliveira, E. B.; E Ferro, R. M. (Cordoba University Press (UCOPress), 2021)
The main of this work was to evaluate the nutritional value of three agroindustrial co-products in finishing diets for sheep using the technique of in vitro gas production. The experimental treatments consisted of the inclusion of three different co-products in the diets: corn germ meal, corn germ meal and sunflower meal at levels of 0, 10, 20 and 30%. The kinetics of cumulative gas production was analyzed using the bicompartmental logistic model. The parameters were analyzed through analysis of variance, and when significant, orthogonal contrasts were used for specific partitioning of the effects of dietary inclusion levels on diets. The addition of maize germ meal in the diets, a quadratic behavior (P <0.05) was observed for the gas production and the rate of degradation of the fast digestion fraction, linear reduction (P <0.05) for the production of gas from the slow digestion fraction and no significant difference (P> 0.05) for the degradation rate of this same fraction. In vitro ruminal digestibility reduced linearly (P <0.05) with inclusion of the levels of this co-product. When dry corn distillery was included in the diets, the production of gases of the fast digestion fraction showed a linear reduction (P <0.05), the degradation rate of this same fraction did not show a significant effect (P> 0.05) (P <0.05) and the rate of degradation of this fraction did not change (P> 0.05). In vitro ruminal digestibility of DM did not change (P> 0.05) with inclusion of this coproduct. The inclusion of sunflower meal resulted in a linear reduction (P <0.05) in the gas production of the fast digestion fraction, a non significant effect (P> 0.05) for the degradation rate of this same fraction, 0.05) for the production of slow digestion fraction and quadratic effect (P <0.05) for the degradation rate of this fraction. There was no significant effect (P <0.05) for ruminal digestibility of dry matter in vitro. It was concluded that although the inclusion of the co-products in the diets altered one or more kinetic parameters of ruminal fermentation, ruminal digestibility in vitro did not change significantly.
Cinética de fermentação ruminal in vitro de diferentes co-produtos agroindustriais utilizados em dietas para ruminantes
Keywords: Corn germ meal; Dried distillers grain of corn; Ruminal degradation; Sunflower meal